Labour: a heterodox approach - Vercherand, Jean (Basingstoke, 2014)
"Labour: A Heterodox Approach provides a theoretical reconstruction of the labour and job market by examining it in a rich historical context. It explores the fundamental implications of the theories of consumption and growth and aims at solving the difficulties raised by the dominant economic theories (neoclassical, Keynesian, supply side) by taking into account the dimension of the historical conflict of the labour market and the public intervention that results from it, such as the construction of a specific legal framework - that is to say, labour law. The work focuses on providing a description of conflict and intervention, the market's leading characteristics, and demonstrates that they can be interpreted by introducing two major remedial hypotheses in economic fundamentals. It also contributes to solving several theoretical controversies and highlights the two main perspectives on the economic regulation of the labour market."